2017
DOI: 10.1111/ceo.13034
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Hill‐radial basis function, Barrett Universal and current third generation formulas for the calculation of intraocular lens power during cataract surgery

Abstract: Acceptable outcomes can be achieved with optical biometry, consistent surgical technique and use of current intraocular lens power calculation formulas. The Barrett Universal II formula may provide the lowest risk of refractive surprise compared with other intraocular lens power calculation formulas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
47
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(49 citation statements)
references
References 34 publications
0
47
0
2
Order By: Relevance
“…In total, there were 4074 eyes enrolled in the 11 included studies (Table 1). 8,[12][13][14][15][16][17][18][25][26][27] The sample size ranged from 24 to 1549 eyes. Most of the studies (n = 9) included patients undergoing cataract surgeries, one trial included patients undergoing refractive lens exchange and one trial included patients with unclear intervention.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations
“…In total, there were 4074 eyes enrolled in the 11 included studies (Table 1). 8,[12][13][14][15][16][17][18][25][26][27] The sample size ranged from 24 to 1549 eyes. Most of the studies (n = 9) included patients undergoing cataract surgeries, one trial included patients undergoing refractive lens exchange and one trial included patients with unclear intervention.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…The primary goal of cataract surgery is the improvement of visual acuity. [13][14][15][16] More recent studies revealed that formulas including Barrett Universal II, Olsen, Haigis, were more accurate. 4,5 The IOL power calculation formulas are less accurate in long eyes, which is commonly defined as AL longer than 24.5 mm, [6][7][8][9] presenting a great challenge for cataract surgeons.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…7,8 In recent years, several multivariable formulas have become increasingly popular with cataract surgeons, including the Barrett Universal II, Olsen and Hill-RBF formulas. 9 While each of these formulas incorporate unique variables and weigh them differently, ACD is nonetheless an important variable in estimating ELP. 10-12,A Given the inclusion of ACD in each of these multivariable formulas, we sought to determine if pupil dilation has an effect on calculated IOL power based on whether biometry measurements are taken in an undilated state as compared to a post-dilated state.…”
Section: Introductionmentioning
confidence: 99%
“…The only currently used IOL calculation approach using Artificial Intelligence is the Hill-RBF formula, which has reported accuracy of 91% of the eyes within ± 0.5 D range from the intended target refraction (Haag-Streit AG Koeniz, 2017). However, there is a number of papers that indicate that Hill-RBF accuracy is not significantly different from the Vergence formula category (Kane et al, 2017;Roberts et al, 2018;Shajari et al, 2018). Unfortunately, there is no publication of the Hill-RBF principle in any peer-reviewed scientific journal, so the only information about the principle itself can be obtained from freely available resources on the Internet.…”
Section: Introductionmentioning
confidence: 99%